(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This article details the process of identifying the Comprehensive Sexuality Education (CSE) contents for children and adolescents with Autism Spectrum Disorder (ASD) and Intellectual Disabilities (ID) while developing a resource booklet for teaching them CSE-related matters in the Nepalese context. People with disabilities are prone to misconceptions and stigma. Likewise, children and adolescents with ASD and ID face an increased risk of exploitation and abuse. Hence, they all deserve equal access to high-quality sexuality education. Nepal’s policy supports inclusive education for learners with disabilities, but its implementation is interrupted due to many issues and obstacles. Therefore, this study aimed to create a CSE resource booklet for Nepalese children and adolescents with ASD and ID, analyzing global sexuality education teaching situations and comprehending the expectations of parents and teachers. The research involved searching documents, conducting focus group discussions with nine teachers and parents of adolescents with ID and eight teachers and parents of adolescents with ASD, and interviewing two teachers and two parents of both categories. The literature reviewed primarily focused on providing body information, appropriate sexual behaviors, relationships, safety, and hygiene. Focus group discussions and interviews revealed that guidance on sexual behavior, self-care, relationship identification, preventing sexual abuse, and menstrual hygiene management are also essential for Nepalese children and adolescents with ASD and ID. The teachers’ resource booklet for teaching sexuality education to children and adolescents with ASD and ID was proposed to include seven main topics and 19 sub-topics, specifically focusing on the Nepalese context for the first time in Nepal.